Effect of high doses of Natuphos E 5,000 G phytase on growth performance of nursery pigs - Gourley, Kiah M (J Anim Sci, 2018)
A total of 360 pigs (DNA 200 × 400, initially 5.9 ± 0.1 kg) were used in a 42 d trial to determine the effect of high doses of a recently available phytase source (Natuphos E 5000 G, BASF Corporation, Florham Park, NJ) on nursery pig growth and bone ash. Pigs were randomly allotted to pens at weaning by BW and pens were allotted to one of eight corn-soybean meal-based dietary treatments in a randomized complete block design. There were five pigs per pen and nine pens per treatment. Diets were fed in three phases (d 0 to 7, 7 to 21, and 21 to 42) with formulated total calcium:phosphorus (Ca:P) of 1.07, 1.05, and 0.93, respectively. Treatments included a negative control (NC) with 0.40, 0.30, or 0.25% aP from monocalcium P for Phases 1, 2, and 3 respectively; and NC with either 500, 1,000, 2,000, 3,000, or 4,000 FTU/kg phytase. The last two treatments were a positive control (PC) with 0.55, 0.45, or 0.40% aP from monocalcium P for Phases 1, 2, and 3, respectively, or PC with 2,000 FTU/kg phytase. The NC diet with 500 FTU/kg and PC without added phytase were formulated to be equivalent in available Ca and P. On d 42, one pig per pen was euthanized and the right fibula was removed for bone ash analysis. From d 0 to 42, pigs fed increasing phytase in the NC tended to have increased (quadratic, P = 0.064) ADG and (linear, P = 0.082) ending BW and had improved (quadratic, P = 0.008) G:F. Adding 2,000 FTU/kg phytase to the PC did not influence ADG or ADFI, but tended to improve (P = 0.060) G:F compared with the PC. In addition, percentage bone ash increased as phytase increased in the NC (linear, P < 0.001) or when 2,000 FTU/kg was added to the PC diets (P < 0.001). Pigs fed the PC had increased (P = 0.007) ADFI and tended to have greater (P = 0.099) percentage bone ash than pigs fed NC+500 FTU/kg phytase, but the pigs fed NC+500 FTU/kg phytase had improved (P = 0.032) G:F compared to pigs fed the PC. In summary, increasing concentrations of dietary phytase in a P-deficient diet improved growth and bone ash measurements, and was optimized at 1,000 FTU/kg. There were varied improvements when 2,000 FTU/kg phytase was added in P adequate diets.